The Myth of Mary Mink: Representation of Black Women in Toronto in the Nineteenth Century - Petrin, Guylaine (Ontario History, 2016)
The tale of Mary Mink, the Black millionaire’s daughter sold into Southern slavery by her white husband and rescued, with great difficulty by her father, is one of the best-known tales of nineteenth-century Toronto. It appeared in contemporary newspapers, has been endlessly retold in scholarly and popular historical publications, and provided some of the subject matter for a made-for-TV movie—even though it is a complete hoax. The origins of the “Minnie” Mink legend are explored in order to understand the context that allowed this blatant falsehood to flourish, and suggest some reasons for its continued acceptance.